ANALISIS SWOT UNTUK PENGEMBANGAN STRATEGI PEMASARAN PRODUK OLAHAN APEL DI MALANG RAYA - Rahayu Relawati; Istis Baroh; Bambang Yudi Ariadi (Universitas Sebelas Maret, 2015)
This study aimed to carry out a SWOT analysis and formulate marketing strategies of processed apple products. Primary data were obtained from producers and consumers. Producers were selected purposively, while consumers were selected by accidental sampling when they bought the product at souvenirs shops of Malang. SWOT analysis was used to analyze the data taken from both producers and consumers, as well as to formulate marketing strategies. The results showed that in general the products of apple chips, porridge and cider have the strength on products, especially in terms of taste. Meanwhile, the weaknesses are less durable products, however, consumers also do not want any preservatives added. Moreover, the opportunities are the high interest of consumers, many souvenir shops and bank credit offered. On the other side, the threats consists of unhealthy business competition and weakness of consumer purchasing power even though they are interested in the products. Based on the results of the SWOT analysis, marketing strategies recommended to the products of apple chips and apple porridge is aggressive strategy, because they are in the first quadrant of SWOT diagram. Apple cider, however, is recommended to run a defensive strategy, because this product is located in quadrant III of the same diagram. Related promotions, various media information such as local television and internet should be used optimally to promote the products. Consumers should receive the correct and fare information, so that producers must conduct a responsible business ethics.